1998
DOI: 10.1097/00007632-199812010-00017
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and Costs of Medical Exercise Therapy, Conventional Physiotherapy, and Self-Exercise in Patients With Chronic Low Back Pain

Abstract: The efficiency of medical exercise therapy and conventional physiotherapy is shown. Leaving patients with chronic low back pain untampered poses a risk of worsening the disability, resulting in longer periods of sick leave.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
118
0
11

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(134 citation statements)
references
References 46 publications
5
118
0
11
Order By: Relevance
“…Injured workers who stopped exercising after a back injury had longer periods of disability than those who remained more physically active (34). Medical exercise therapy and conventional physical therapy reduce the cost of low back pain, even in chronic cases (35). However, intensive multidisciplinary treatment is not necessarily more effective than a less intensive exercise program (36).…”
Section: Discussionmentioning
confidence: 99%
“…Injured workers who stopped exercising after a back injury had longer periods of disability than those who remained more physically active (34). Medical exercise therapy and conventional physical therapy reduce the cost of low back pain, even in chronic cases (35). However, intensive multidisciplinary treatment is not necessarily more effective than a less intensive exercise program (36).…”
Section: Discussionmentioning
confidence: 99%
“…While all scored reasonably well in the bias and reporting aspects, measurement and reporting of confounding showed considerable variability. The highest ranked study [55] found that walking did not have a statistically significant affect on LBP, while conversely the three lowest ranked studies [25,36,54] found walking combined with traction had a positive effect.…”
Section: Duration Of Lbp 1-6 Monthsmentioning
confidence: 95%
“…Two RCT's [36,55], one case-control [54] and one cohort study [25] were found. While three laboratory-based studies used a treadmill [25,36,54], only one study evaluated walking in free living [55].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations